No-till and nitrogen management improve soybean yield by increasing the net photosynthetic rate in an arid area of northwest China - Zhang, Kangxu; He, Huangcheng; Jiao, Jinbao; Liu, Jianguo (Frontiers in Agronomy, 2025)
No-till (NT) farming minimizes disturbance to agricultural ecosystems and regulates the water cycle in dryland agriculture. This study investigated the interactive effects of tillage practices and nitrogen (N) application on soybean (Glycine max L.) photosynthesis and yield to optimize N management in NT systems. Field experiments (2023–2024) in Shihezi, Xinjiang, employed a split-plot design with tillage (conventional tillage, CT; no-till, NT) as main plots and N rates (0, 105, 150, 195 kg N ha-¹; denoted N0, N1, N2, N3) as subplots, generating eight treatments (CTN0, CTN1, CTN2, CTN3, NTN0, NTN1, NTN2, NTN3). The NTN2 system significantly increased soil water storage (SWS) and soil total nitrogen (STN) relative to NTN0 (P < 0.05), enhanced soybean leaf area index (LAI) during R4-R6 stages, and improved SPAD values, net photosynthetic rate (Pn), and stomatal conductance (Gs), ultimately boosting grain yield (GY) by 75.7–83.4% versus NTN0 (P < 0.05). Crucially, N2 application mitigated tillage-induced constraints, enabling NT to achieve yields comparable to CTN2 (P > 0.05). Thus, integrating no-till with 150 kg N ha-¹ optimizes soybean productivity and resource efficiency in arid northwestern China.